Are the Fathers Alright? A Systematic and Critical Review of Studies on Gay and Bisexual Fatherhood - Carneiro, Francis A.; Tasker, Fiona; Salinas-Quiroz, Fernando; Leal, Isabel; Costa, Pedro A. (Frontiers in Psychology, 2017)
The purpose of the present systematic and critical review was to assess the findings and to identify the gaps in the literature concerning gay and bisexual fathers. A comprehensive search of relevant literature using electronic databases and reference lists for articles published until December 2016 was conducted. A total of 63 studies, spanning from 1979 to 2016, were collected. More than half of the studies were published after 2011 and the overwhelming majority were conducted in the United States. Nine themes were identified in the studies reviewed: (1) Pathways to fatherhood; (2) Motivations for fatherhood; (3) Parenting experiences and childrearing; (4) Family life and relationship quality; (5) Gender and father identities and gender-role orientation; (6) Disclosure of sexual identity; (7) Social climate; (8) Father’s psychosocial adjustment; and (9) Children’s psychosocial adjustment. It was found that research on gay fatherhood appears to be more heterogeneous than on lesbian motherhood, perhaps because of the variety of pathways to parenthood (via co-parenting, adoption, fostering, or surrogacy). Two-father families are becoming more visible in research on sexual minority parenting and gradually transforming the conceptualization of parenting in family research.